Efficient hydrogenation catalysts of Ni or Pd on nanoporous carbon workable in an acidic condition - Lee, Donghwan; Kim, Honggon; Kang, Min; Kim, Ji Man; Lee, Ik-Mo (WILEY-V C H VERLAG GMBH, 2007)
Efficient catalytic systems, where Ni or Pd is introduced in a supporting material of nanoporous carbon, have been developed for a liquid-phase hydrogenation of carboxylic acids and ketones at room temperature. It has been found that the catalysts reliably show high activities and selectivities for the hydrogenation to alcohols even in acidic conditions, and the catalytic activities depend on the preparative method of catalysts, the hydrogen pressure, the agitation rate, and the catalytic species. The hydrogenation of carboxylic acids and ketones clearly shows that the reaction rate is affected by the electronic and the steric effects, and a plausible reaction mechanism using metal hydrides as catalytic species is proposed.
Keywords: NICKEL(II) ION; SPHERES